2017
DOI: 10.1016/j.neuron.2017.07.036
|View full text |Cite|
|
Sign up to set email alerts
|

Input-Timing-Dependent Plasticity in the Hippocampal CA2 Region and Its Potential Role in Social Memory

Abstract: Summary Input-timing dependent plasticity (ITDP) is a circuit-based synaptic learning rule whereby precisely timed, paired activation of direct entorhinal cortex (EC) and Schaffer collateral (SC) inputs to hippocampal CA1 pyramidal neurons (PNs) produces a long-term enhancement of CA1 SC excitation, which has been linked to specificity of contextual memory. We report that paired activation of EC and SC inputs also increases SC excitation of CA2 PNs, which are important for social memory. However, whereas CA1 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 60 publications
(115 reference statements)
7
78
1
Order By: Relevance
“…Our results contradict previous studies that report no IEG induction in the CA2 region of the hippocampus upon social stimuli Tanimizu et al, 2017), while supports findings from Kim et al that report CA2 activation upon social interaction (Kim et al, 2015). The hippocampus is critically integrated into the rodent circuitry involved in social behaviours (Kim et al, 2015;Ko, 2017;Kogan et al, 2000;Raam et al, 2017;, but specifically, the CA2 subfield is important for the formation of social memory Hitti and Siegelbaum, 2014;Leroy et al, 2017;Lin et al, 2017;Smith et al, 2016;Stevenson and Caldwell, 2014). Therefore, it is no surprise that we observe neuronal activation in the CA2 region upon social stimuli, a prerequisite to social memory formation (Felix-Ortiz and Tye, 2014;Hitti and Siegelbaum, 2014).…”
Section: Discussionsupporting
confidence: 66%
“…Our results contradict previous studies that report no IEG induction in the CA2 region of the hippocampus upon social stimuli Tanimizu et al, 2017), while supports findings from Kim et al that report CA2 activation upon social interaction (Kim et al, 2015). The hippocampus is critically integrated into the rodent circuitry involved in social behaviours (Kim et al, 2015;Ko, 2017;Kogan et al, 2000;Raam et al, 2017;, but specifically, the CA2 subfield is important for the formation of social memory Hitti and Siegelbaum, 2014;Leroy et al, 2017;Lin et al, 2017;Smith et al, 2016;Stevenson and Caldwell, 2014). Therefore, it is no surprise that we observe neuronal activation in the CA2 region upon social stimuli, a prerequisite to social memory formation (Felix-Ortiz and Tye, 2014;Hitti and Siegelbaum, 2014).…”
Section: Discussionsupporting
confidence: 66%
“…Similar to our findings, Finlay et al show that genetic removal of NMDRs from the dorso-lateral hippocampus (inclusive of CA2 and CA3 neurons) in adulthood resulted in no effect on social novelty preference, which requires social memory (Finlay, Dunham et al 2015). Furthermore, although pyramidal CA2 neurons do not respond to standard long-term potentiation inducing protocols, it was recently observed that input-timing dependent plasticity can occur, but that this change in pyramidal neuron response is driven by long-term depression of adjacent parvalbumin (PV) interneurons in the CA2 region (Dudek, Alexander et al 2016, Leroy, Brann et al 2017). Blocking delta opioid receptors, which are found on PV interneurons in the CA2, was able to block the depression in the PV interneurons, the potentiation in the pyramidal neurons and short-term social memory (Leroy, Brann et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given the known layered organization of entorhinal, septal and supramammillary inputs at SLM and SO (Soussi et al, 2010;Joshi et al 2017), our data suggest distal CA2 cells may be biased towards extra-hippocampal theta generators, while proximal CA2 cells rather follow intra-hippocampal CA3 influences. Proximodistal differences of I/E balance and unique plasticity properties of different pathways may further contribute (Piskorowski and Chevaleyre 2013;Nasrallah et al 2016;Dasgupta et al, 2017;Leroy et al, 2017;Sun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The CA2 hippocampal region has distinctive molecular, physiological and connectivity properties . CA2 pyramidal cells respond vigorously to direct entorhinal inputs from layer II stellate cells Leroy et al 2017). In addition, they receive a direct mossy fiber connection from granule cells and contribute to a parallel trisynaptic circuit to deep CA1 sublayers (Kohara et al, 2014;Sun et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation